Makna Simbolik Zakat dalam Perspektif Nurcholish Madjid - wiwin wiwin (Direktorat Jenderal Bimbingan Masyarakat Islam, 2016)
Abstraksi Zakat adalah salah satu ajaran Islam yang berkenaan dengan harta. Ia tidak hanya menyangkut urusan dengan Tuhan, tapi juga menyangkut urusan dengan sesama manusia. Zakat –sebagaimana juga ajaran-ajaran agama lainnya– dalam pandangan Nurcholish Madjid merupakan simbol keagamaan dan karenanya memiliki makna simbolik. Meneliti makna simbolik zakat dalam perspektif Nurcholish Madjid ini cukup menarik dan penting, Oleh karena itu dalam penelitian ini penulis fokus pada kajian tentang makna simbolik zakat dalam perspektif Nurcholish Madjid. Metode yang penulis gunakan dalam penelitian ini adalah analisis wacana, sebab hampir semua sumber data merupakan teks. Hasil penelitian menunjukkan bahwa zakat dalam pandangan Nurcholish Madjid merupakan wujud keshalehan sosial sebagai konsekuensi logis dari adanya keshalehan pribadi. Abstract Zakat is one of Islamic doctrines that concerning the property. It is not only concerned with the affairs of the Lord, but also concerning dealings with human being fellows. Zakat –as well, just as the others religious teaching— in Nurcholish Madjid’s perspective is a religious symbol and therefore has a symbolic meaning. Examining the symbolic meaning of zakat in Nurcholish Madjid’s perspective is quite interesting and important, Therefore, in this study the writer focused on the study of the symbolic meaning of zakat in Nurcholish Madjid’s perspective. The method that the writer used in this research is discourse analysis method, because almost all the data source is a textual form. The results showed that zakat in Nurcholish Madjid’s perspective is a form of social piety as a logical consequence of their personal piety.